The Current Status of Circular Economy Development in the Mekong Delta - Thanh Nha, Huynh; Thi Thu An, Nguyen; Oanh, Dinh Thi Kieu; Buu Minh Quan, Le (VNU Journal of Science: Policy and Management Studies; Vol 41 No 1, 2025)
Transitioning to a circular economy aims to reduce resource exploitation, limit pollution, and promote sustainable development, ensuring a balance between economic growth and environmental protection. This has become a key development trend across various production industries. Over time, the Mekong Delta has implemented various circular economy models such as rice-shrimp farming, water circulation, plastic and agricultural waste recycling. However, implementation remains inconsistent, and few circular economy models have received high-tech investment. Therefore, developing a circular economy model requires close coordination between the government, businesses, and communities, integrated with Industry 4.0 to create sustainable value and long-term efficiency.